(3GdYHGH GdRGNQ hGddHGH GdaGNQs - (3QVj GdOjf CHj GdaVGFd GdMSf Hf eMeO CHh GdMSf, MjOQ GdUGZGfj, J (B650 (3g` s ((3HjJ Gddg GdMQGe s)
(3ChdgG (B:s
(3ef aUd GdYjf (B( (3ef HGH GdVGO(B) (3eGOI ZHV , bhdg (B: (3GddjK(B: (3GdJZHjV Cf jQjO GdEfSGf GdHcGA adG JLjHg GdYjf s
(3BNQgG (B:s
(3ef aUd GdjGA HGH GdWGA eGOI jYW hbGd ZjQg (B: (3jYGW (B( (3HVe GdjGA(B) (3dZI KGdKI hCjYWJ HGdPFH hjYWJ Hg JjYjWkG hjGYWJ Hg EPG bdJ dg jYGW BNQ MQha GdWGA ef cJGH (B: (3GdYHGH hddg GdMeO s
(3GdeNWhW eYLe ai GddZI Cdag dGHf GdYdbei hRjQ GdeSJYUes
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B214s
Keywords: (3GddZIs